New science, or old myth? - Aytbayev, O.; Temirbulatova, A.K. (Вестник Карагандинского университета, 2016)
This article deals with the correlation of science and extra sensorial perception of the world. It is claimed the scientific perception of the world radically differs from extra sensorial perception. The science or scientific perception is a sphere of human activity function of which is development and theoretical schematization of objective reality knowledge. And, the extra sensorial perception belongs to the perception forms occurring without participation of sense organs and belonging to area of mysticism. The mysticism is the base of myth perception. The myth or myth perception are parts of culture. The culture is broader concept than science, the «pseudoscientific myths» demand, probably, a double assessment — criticism as the area applying to be science, and the analysis as a part of culture which can't be ignored and which is difficult interwoven into human knowledge.
Keywords: mysterious; extra sensorial perception; biofield; science; myth; legend; folk tale; fairytale; fable; folklore; bylichka; mysticism